2009
DOI: 10.4025/reveducfis.v20i2.4385
|View full text |Cite
|
Sign up to set email alerts
|

Excesso de peso e pressão arterial em adolescentes de João Pessoa-PB

Abstract: Analisou-se a associação entre o índice de massa corporal (IMC) e a pressão arterial (PA) em adolescentes do município de João Pessoa-PB, Brasil. A amostra foi composta por 303 rapazes e 379 moças, de 14 a 17 anos de idade. Foram coletadas informações sociodemográficas (sexo, idade, classe econômica, escolaridade do chefe de família), peso e estatura auto-referidos (determinação do IMC), medidas de PA sistólica e diastólica, atividade física, hábitos alimentares e fumo. A razão de prevalência (RP), com respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…In our study, higher diastolic blood pressure was found in girls, compared to males, and FFM was higher among boys who had high systolic blood pressure, probably because the increased muscle mass was greater in male adolescents. Weight gain and high body fat can significantly contribute to high blood pressure even in individuals classified as normotensive 27. Systolic blood pressure of adolescents in this study was associated with higher mean values of FMI and its corresponding mass for both sexes.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In our study, higher diastolic blood pressure was found in girls, compared to males, and FFM was higher among boys who had high systolic blood pressure, probably because the increased muscle mass was greater in male adolescents. Weight gain and high body fat can significantly contribute to high blood pressure even in individuals classified as normotensive 27. Systolic blood pressure of adolescents in this study was associated with higher mean values of FMI and its corresponding mass for both sexes.…”
Section: Discussionmentioning
confidence: 44%
“…Em nosso estudo verificou-se maior pressão arterial diastólica em meninas, comparadas com o sexo masculino, e a MLG foi maior nos rapazes que apresentaram pressão arterial sistólica elevada, provavelmente porque o aumento da massa muscular foi mais acentuado nos adolescentes do sexo masculino. O ganho de peso e a adiposidade corporal elevada podem contribuir significativamente para a elevação da pressão sanguínea mesmo em indivíduos classificados como normotensos 27. A pressão arterial sistólica dos adolescentes deste estudo associou-se com valores médios maiores do IMG e sua massa correspondente para ambos os sexos.…”
Section: Discussionunclassified
“…Weight gain and high body fat can significantly contribute to high blood pressure even in individuals classified as normotensive. 27 Systolic blood pressure of adolescents in this study was associated with higher mean values of FMI and its corresponding mass for both sexes. According to Jessup and Harrell, 28 systolic blood pressure increases in pubertal stage, regardless of age, particularly in girls.…”
Section: Discussionmentioning
confidence: 45%
“…O ganho de peso e a adiposidade corporal elevada podem contribuir significativamente para a elevação da pressão sanguínea mesmo em indivíduos classificados como normotensos. 27 A pressão arterial sistólica dos adolescentes deste estudo associou-se com valores médios maiores do IMG e sua massa correspondente para ambos os sexos. Segundo Jessup et al ., 28 a pressão arterial sistólica aumenta na fase púbere, independentemente da idade, particularmente em meninas.…”
Section: Discussionunclassified